Pengelolaan Sampah Rumah Tangga Non Organik Melalui Bank Sampah di Desa Tumang Kecamatan Cepogo Kabupaten Boyolali - Atiqoh Retno Dewi; Sri Hartini (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Disposing of household waste carelessly has become a habit for some people in Tumang Village, thus making the environment polluted. Therefore, a change in the community’s paradigm regarding waste banks needs to be carried out in a sustainable manner. Awareness education and community skills for waste management is very important. Waste bank based on citizen participation is social capital in community-based waste management. Waste bank done in Tumang, Cepogo, Boyolali, Indonesia as a form of concern for the community. Waste bank activity is a concept of collecting and sorting non-organic waste. Empowerment of citizens is carried out through several activities such as educational outreach, training with participatory methods (interaction and communication), as well as dialogue with residents in the community. This waste bank provides benefits to resident, such as reduced waste piles, a clean and healthy environment, and economic independence for residents. Integrated waste management can stimulate creativity and innovation from the community so as to improve the welfare of residents.